Education-Vocational Implications of Field-Dependence-Independence for Secondary School Graduates - Koroluk, Lorne E. (Canadian Journal of Counselling and Psychotherapy, 2011)
A number of educational-vocational variables were examined in relationship to field dependence-independence of individuals completing secondary school and entering occupations or educational programs. The variables included: senior secondary school course selection; academic success in the graduation program; nature of and satisfaction with educational-vocational involvement two to three years after school leaving; and perceptions of most favored, least favored, and, career-wise, most useful school subject. Data were available for 117 who graduated, 68 of whom volunteered educational-vocational details two to three years after graduating. It was concluded that field dependence-independence as measured by the Group Embedded Figures Test does have potential for academic and vocational counselling at the secondary school level, particularly in conjunction with other procedures such as those developed by Holland. It was apparent that gender is also a potent factor implicated in the selection of school subjects and subsequent involvement in careers.